The Value of Moral Education in the Movie Jejak Suara Adzan and Its Relevance to Islamic Religious Education - Muhammad Najib Fanani; Evi Nurliana; Syarifah Ainun; Muhammad Sopyan (Advance Journal of Education and Religion (AJER) published by Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2024)
Moral education also plays a role in the process of forming a society with character, ethics and aesthetics in social life through the transfer of values contained therein. The purpose of this study was to determine the moral values in the sound track of the call to prayer, to determine the relevance of the sound track of the call to prayer to Islamic religious education. This research is a library research, which uses a qualitative descriptive method. Data were obtained from each character’s dialogues and actions related to moral education values in the film. Based on the research conducted, it shows that the values of moral education are contained in the sound track of the call to prayer, namely moral values towards Allah SWT, Rasulullah SAW, and Humans. The film also has relevance to Islamic religious education which includes the six pillars of faith, this film is relevant for parents, adults and youth with parental guidance